PEDAGOGICAL ASPECTS OF DEVELOPING A CULTURE OF INDEPENDENT THINKING IN FUTURE TEACHERS BASED ON PHILOSOPHICAL DISCIPLINES (Scientific journal of the Fergana State University, 2025)
The article analyzes the interactive pedagogical aspects of educational technologies aimed at the development of a culture of independent thinking of future teachers based on interactive teaching of philosophy, problem-based learning and the analysis of problem situations, and interactive methods such as "Blitz-survey", "SWOT-analysis", "Discussion", "FSMU", "Intellectual duel", "Dispute of ideas", which are widely used in practice in developing a culture of independent thinking of future teachers; "Intellectual attack", "Boomerang", "Stairway-stairway".